Development of a dialogue-based guidance system for narrow area navigation. Issue 4 (July 2021) - Yoshida, Yasuhiro; Masui, Fumito; Ptaszynski, Michal
Highlights: We proposed an efficient way to navigate the facility through the dialogue. Our navigation method is applicable even if there are not enough objects containing text in the target location. About 96% of the experiment participants were able to reach their destination. We were able to accurately obtain the information on location from dialog. The shortest route in terms of distance was found to be effective. Abstract: In this paper, we propose a dialogue-based navigation system for narrow areas (e.g., buildings, etc.). In particular, we develop Campus Navigation Partner System (CNPS), intended for the use by freshmen (first-year students) who are likely to get lost in the new environment on the university campus (with the campus of Kitami Institute of Technology set as the experimental environment). The CNPS operates on a smartphone and has the functions of facility navigation and indoor information presentation. Indoor environment navigation is typically a problematic task because GNSS (Global Navigation Satellite System) signals cannot be received with sufficient accuracy within concrete walls. Therefore, we utilized natural language dialogue as a navigation method that guides the users within the facility using navigation messages and images. To investigate the effectiveness of the constructed system, we conducted practical experiments with freshmen and senior students of the university and evaluated the performance of the navigation functionality. Moreover, we investigated the general impressions of the system which we evaluated separately with both freshmen and senior students to clarify the differences in evaluation viewpoints between freshmen and users experienced in the campus environment (graduate students, etc.).